Variability in Sarocladium oryzae, incitant of sheath-rot of rice (Oryza sativa) - PHOOKAN, A K; HAZARIKA, D K (The Indian Journal of Agricultural Sciences, 2013)
Eight isolates of sheath-rot pathogen [Sarocladium oryzae (Sawada) Games & Hawksworth] of rice (Oryza sativa L.) were collected from various rice-growing areas of north-east India and subjected to micrommphological, cultural, physiological and pathological tests to ascertain the variability in the pathogen. Morphomctric variation among the isolates was not significant. The isolates responded differentlyto different media, temperature and pH levels. Pathogenic variability among the isolates was significantwhen tested on 8 rice genotypes. Based on different cultural, physiological and pathological tests, the isolates were categorized into 3 distinct groups, which signified the existence of races or biolypes within the morphological species of the pathogen.